2017
DOI: 10.5943/mycosphere/8/10/6
|View full text |Cite
|
Sign up to set email alerts
|

Mycosphere notes 51-101. Revision of genera in Perisporiopsidaceae and Pseudoperisporiaceae and other Ascomycota genera incertae sedis

Abstract: This is the second in a series, Mycosphere notes, wherein we provide notes on various fungal genera. In this set of notes we deal with genera of the families Perisporiopsidaceae and Pseudoperisporiaceae. These families have traditionally accommodated taxa associated with dead and living leaves of mostly tropical plants and comprised pathogens, saprobes or epiphytes. Most genera are poorly understood with only brief Latin descriptions, but molecular sequence data are needed to establish their taxonomic placemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(52 citation statements)
references
References 23 publications
0
52
0
Order By: Relevance
“…Alina is similar to Tretospora (the asexual morph of Balladynopsis) based on some hyphomycetous conidial structures found on the ex-isotype of Alina jasmini (Sivanesan 1981). By re-examining the same specimen, Boonmee et al (2017) reported that they were unable to find some structures e.g. setae, hyphopodia-like structures or even conidia as previously shown in Raciborski (1909) and Sivanesan (1981).…”
Section: Dothideomycetes Families Incertae Sedismentioning
confidence: 61%
See 4 more Smart Citations
“…Alina is similar to Tretospora (the asexual morph of Balladynopsis) based on some hyphomycetous conidial structures found on the ex-isotype of Alina jasmini (Sivanesan 1981). By re-examining the same specimen, Boonmee et al (2017) reported that they were unable to find some structures e.g. setae, hyphopodia-like structures or even conidia as previously shown in Raciborski (1909) and Sivanesan (1981).…”
Section: Dothideomycetes Families Incertae Sedismentioning
confidence: 61%
“…setae, hyphopodia-like structures or even conidia as previously shown in Raciborski (1909) and Sivanesan (1981). They concluded that Alina has unique characters and could not be placed in any families in Dothideomycetes (Boonmee et al 2017). Thus, they established Alinaceae to accommodate this genus.…”
Section: Dothideomycetes Families Incertae Sedismentioning
confidence: 99%
See 3 more Smart Citations